Supply chains - Liu, J (Edward Elgar, 2013)
Transport activities are usually divided into passenger and freight transport. Freight transport and associated logistics and supply chains constitute an important component of the modern transport system and have been regarded as fundamental elements for global economic growth. With the extension of globalization, freight transport is expected to be profoundly impacted and shifted by the changing economic demand. This chapter discusses some key issues within the freight transport and supply chains sector, including a brief introduction to global supply chain development history, the relationship between a supply chain and the modern economy, typical supply chain initiatives that affect the cost efficiency and energy intensity of freight transport operations, future freight transport development and their implications on low carbon mobility. A supply chain should encompass all the activities involved in the planning and management of a transport system required for the production and supply of a good or service to consumers, and it consists of a network that includes people, technology, activities, information and resources.